Pertimbangan dan Sikap Milenial terhadap Minat Menggunakan E-Wallet: Pada Masa PSBB Pandemi Covid-19 di Kota Tangerang - Humairoh Humairoh; Andi Kasuma Negara; Siti Asriah Immawati (Universitas Winaya Mukti, 2020)
The government's policy to prevent or reduce the spread of the Covid-19 virus is to enforce the Large-Scale Social Restrictions (LSSR) so that transactions that previously use paper money and cash turn into digital transactions. So far, e-wallets are considered as a transaction facility that makes it easier for users. This study aims to analyze the differentiation attributes that affect millennial considerations and attitudes towards usability to intention to use e-wallets during LSSR Covid-19 on millennials in Tangerang City. The research sample was 96 respondents using purposive sampling technique, namely millennials who use e-wallets in making payments. The instrument used was a structured questionnaire with a Likert scale of 1-5, data processing using the Smart PLS program. This study's results, the intention to use e-wallet of the millennial generation, were influenced by brand image, perceived ease of use, perceived usefulness through millennial consideration, and attitudes toward usability as intervening variables with R2 adjusted 0.638. This study's results have implications for SMEs business actors to switch payment systems from cash payments to payments using e-wallets.